Comparison of Growth Performance and Carcass Quality of KUB Kampung Chicken, Merawang Chicken, and In-ovo Feeding Kampung Chicken - Iful, Saifullah; Pakiding, Wempie; Dagong, Muh. Ihsan A.; Teguh, Muhammad (State Islamic University of Sultan Syarif Kasim Riau, 2024)
ABSTRACT. This study aims to determine the growth performance and carcass quality of three different Kampung chicken species (KUB Kampung Chicken, Merawang Chicken, and In-ovo Feeding Kampung Chicken). This research was conducted at the CV. Bittara Wanua in Soppeng Regency. The study followed a Completely Randomized Design (CRD) with three treatments and five replication plots. Each replication plot contained 5 chickens. The treatments namely: P1 uses KUB chicken, P2 uses Merawang chicken, and P3 uses Kampung chicken from in-ovo feeding. The parameters observed were growth performance including body weight gain, feed consumption, and feed conversion, while carcass quality includes carcass percentage, breast percentage, upper thigh percentage, lower thigh percentage, wing percentage, and back percentage. The results showed that treatment had a significant effect (P<0.05) on body weight gain, feed conversion, breast percentage, lower thigh percentage, and back percentage. Still, they had no effect (P>0.05) on feed consumption, carcass percentage, upper thigh percentage, and wing percentage. It could be concluded that KUB chicken has the best growth performance and carcass quality because it has fast growth, low feed conversion, and a high percentage of carcass parts of the breast compared to other types of native chickens.